Parallel And Distributed Calculations Supported And Managed By The Relational Database - Piotr Oramus (Computer Science, 2009)
A simple, based on a relational database, system, for a management of a parallel and a distributedcomputer calculations, is presented. In the proposed system, the parallel calculationsare carried out according to a master/slave model. Because an input and an output data ofprograms are stored directly in the database, the use of files is reduced to a minimum. Themanagement system allows for a combination of computing power of many computers forsolving a single numerical problem.